PENERAPAN PRINSIP GOOD CORPORATE GOVERNANCEPADA KOPERASI MODERN - Wahyuni Safitri (Yuriska: Jurnal Ilmiah Hukum, 2026)
Modern cooperatives are increasingly required to implement professional, transparent, andaccountable governance in response to the growing complexity of business activities andpublic accountability. This study aims to examine the implementation of Good CorporateGovernance (GCG) principles within the Indonesian cooperative legal systemandtoformulate an ideal model for strengthening GCG-based regulation and cooperativegovernance. This research employs normative legal research methods using statutory, conceptual, and comparative approaches, through an analysis of Law Number 25 of 1992onCooperatives, its implementing regulations, and legal doctrines on corporate governance. The findings reveal that the principles of GCG have been normatively accommodatedintheIndonesian cooperative legal framework, particularly through economic democracy, theresponsibilities of cooperative management, and accountability mechanisms withinthegeneral meeting of members. However, such regulation remains implicit, fragmented, andlacks comprehensive governance standards comparable to those applied in modern corporateentities. Furthermore, this study proposes that an ideal model for strengthening GCG-basedcooperative regulation and governance should be developed through the reformof cooperative legislation that explicitly incorporates the principles of transparency, accountability, responsibility, independence, and fairness; the enhancement of the roles andprofessionalism of cooperative organs; and the establishment of modern cooperativegovernance guidelines aligned with cooperative values and identity. This model is expectedto promote legally sound, ef iciently managed, and sustainable cooperatives with enhancedcompetitiveness within the national economic system